Development Of Total Maximum Daily Load By Using Water Quality Modellling As An Approach To Investigate The Quality Of Water In Sungai Batu Pahat : TMDL - Syahiran Bin Samsuri,; Mohd. Shalahuddin Bin Adnan, (Recent Trends in Civil Engineering and Built Environment, 2021)
River has become one of the most important water sources for human being and environment uses. However, due to the rapid development and urbanization, it have increase the pollutant loads in the river. Therefore, there are  several approaches have been implemented in order to overcome water pollution issues and for river basin management such as Integrated River Basin Management (IRBM) and Total Maximum Daily Load (TMDL). This study attempts to quantify six selected water quality parameters (pH, DO, BOD, COD, NH3-N, TSS) and to develop the TMDL implementation plan with the application of water quality modelling tools. There are 6 parameters used to determine the WQI, which are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3), Acidic and Alkaline (pH), Dissolved Oxygen (DO), Total Suspended Solids (TSS). On the other hand, the water flow velocity of the river also being measured on site, and the water flow and water quality modelling were simulated by using Qual2K water quality modelling software. From the data observed, it shows that the commercial sector of landuses have become the most contributor towards the pollution loading (kg/day) in Batu Pahat River, which mainly come from CP1 Fisheries, CP3 Workshops, CP4 Wet Market, CP5 Restaurant, CP6 Workshop, and CP7 Workshop. In addition, high tide flow produced higher pollution load (kg/day) compared to low tide flow due to larger amount of discharge during high tide flow. The simulation for both low tide and high tide flow demonstrates that when DO concentration input is higher, there will be decrease in the concentration of COD, BOD, TSS, and NH3-N. As a conclusion, the development TMDL plan with the helps of QUAL2K water quality modelling, helps to improve the water quality condition at Batu Pahat River by using pollution loading reduction analysis and for future watershed management.